Fisheries, fisheries management, and institutional context: the case of flounder in Argentina (1989–2020) (Huellas, 2026)
Flounder is a demersal resource of commercial interest in Argentina and is part of the group known as variado costero. This study analyses the evolution of flounder landings in Argentina between 1989 and 2020, identifies significant changes in the time series, and discusses these changes in relation to fisheries management measures, the regulatory framework, and the institutional context of the activity. Official landing statistics were used, and the Mann-Kendall test, Sen’s slope estimator, and breakpoint analysis were applied. The results showed a significant downward trend in landings and allowed the identification of four sub-periods: boom (1989-1998), crisis (1999-2004), partial recovery (2005-2012), and intensification of the crisis (2013-2020). Although a relative improvement was recorded during the third sub-period, coinciding with the implementation of management and regulatory measures, this trend was not sustained over time, and the final stage showed the lowest mean values in the entire series. Overall, the results suggest that the evolution of this fishery cannot be interpreted only in biological terms, but also in relation to exploitation patterns and the regulatory and management instruments applied over time.